Unpacking attitudes of grade 12 SHS academic track students towards speaking English: an exploratory study - Sheryl D. Delima (Science and Education, 2023)
This study explores the attitudes and challenges of senior high school students towards English language learning in a private institution in the Philippines. A mixed-methods approach was utilized, which included a survey questionnaire and a focus group discussion with selected participants. The findings reveal that the majority of the participants had a positive attitude towards English and recognized its importance in communication, education, and career advancement. However, they also acknowledged the challenges they faced in speaking English, such as lack of confidence, limited vocabulary, and difficulty in pronunciation. The participants also recognized the role of culture in English language learning and believed that their cultural background and experiences influenced their attitudes and proficiency in the language. The study concludes that while the participants had a positive attitude towards English, they also faced challenges in learning the language. Therefore, there is a need for English language educators to address these challenges and provide support for students to improve their proficiency in English.